Angels tapping at the wine-shop's door a history of alcohol in the Islamic world - Matthee, Rudolph P. 1953- (Hurst Publishers, 2023)
1. Islam and Alcohol -- 2. Alcohol in the Premodern Islamic World (c. 600 to c. 1400) -- 3. Wine in Islamic Painting, Poetry, and Adab Literature -- 4. Alcohol in the Early Modern Islamic Empires: The Ottomans and the Mughals -- 5. Alcohol in the Early Modern Islamic Empires: The Safavids -- 6. Changing Drinking Habits in the Nineteenth Century- Part One: The Ottoman Empire and North Africa -- 7. Changing Drinking Habits in the Nineteenth Century- Part Two: Qajar Iran -- 8. Alcohol in the Modern Age: New Drinks and Drinking Customs-Part One: The Arab World -- 9. Alcohol in the Modern Age: New Drinks and Drinking Customs-Part Two: Turkey, Iran, and Pakistan -- Conclusion